2016
DOI: 10.1186/s13662-016-0830-6
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative behavior of a smoking model

Abstract: We study the qualitative behavior of a smoking model in which the population is divided into five classes, that is, non-smokers, smokers, people who temporarily quit smoking, people who permanently quit smoking, and people who are associated with illness due to smoking. The global asymptotic stability of the unique positive equilibrium point is presented. More precisely, a graph-theoretic method is used to prove the global stability of the unique positive equilibrium point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…Based on the discussion in [21], it can be concluded that all the roots of Eq. (6) have negative real parts.…”
Section: Local Stability and Existence Of Hopf Bifurcationmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the discussion in [21], it can be concluded that all the roots of Eq. (6) have negative real parts.…”
Section: Local Stability and Existence Of Hopf Bifurcationmentioning
confidence: 99%
“…Thus, it is reasonable to consider the smokers associated with some illness compartment in giving up smoking model. Based on this point, the following smoking model has been proposed by Din et al [21]:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ma et al developed different forms of heroin epidemic models [3,[6][7][8][9][10] to study the transmission of heroin epidemics. Sharomi et al formulated different smoking models [11][12][13][14][15][16][17] for giving up smoking. There were also some drinking models [18][19][20][21] proposed by Mushayabasa et al to analyze the influence of binge drinking to public health.…”
Section: Introductionmentioning
confidence: 99%
“…In [1], a smoking model that considers the number of individuals who are aware of the bad effects of smoking through education or media campaign was presented. Din [8] studied a smoking model considering non-smokers, smokers, people who temporarily or permanently quit smoking and people who are associated with illness due to smoking.…”
Section: Introductionmentioning
confidence: 99%